'A powerful, spiritual, win-win situation': commercial authenticity in professional birth photography. (July 2022) - Ribak, Rivka; Leshnick, Anat
Against a background of occlusion and medicalized portrayals, the emergent practice of birth photography allows women to see and to depict birth from their own perspective. Thus the delivery room, the digital camera, and the direct encounter between the artisan and her client enable exploring the possibility of alternative depictions in a neoliberal economy, and the significance of professionalism in a field dominated by expert amateurs. Drawing upon interviews with photographers and clients, our analysis highlights three tensions underlying birth photography as a documentary and entrepreneurial pursuit: the formulaic depiction of an extraordinary event; the exposure of an intimate experience; and the commercialization of the sacred. We find that in terms of content, birth photographs present restrained, conventional depictions, suitable for both the family album and the photographers' social media portfolios. In terms of practice, although desired by their clients, birth photographers' work is unstable and they must constantly invest in relational labor that balances intimacy and publicness, friending and advertising. We propose the notion of commercial authenticity to capture this contradictory amalgam of disciplined realism, edited documentation, and professional closeness that both clients and photographers expect, produce, and regard as appropriate in the context of artisanal photography.